2016
DOI: 10.1038/srep18408
|View full text |Cite
|
Sign up to set email alerts
|

Nesterenkonia sp. strain F, a halophilic bacterium producing acetone, butanol and ethanol under aerobic conditions

Abstract: The moderately halophilic bacterium Nesterenkonia sp. strain F, which was isolated from Aran-Bidgol Lake (Iran), has the ability to produce acetone, butanol, and ethanol (ABE) as well as acetic and butyric acids under aerobic and anaerobic conditions. This result is the first report of ABE production with a wild microorganism from a family other than Clostridia and also the first halophilic species shown to produce butanol under aerobic cultivation. The cultivation of Nesterenkonia sp. strain F under anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The Nesterenkonia sp. strain F was cultivated in petri‐dish consisting of (g/L): NaCl, 10; MgCl 2 , 7; MgSO 4 , 9.6; CaCl 2 , 0.36; KCl, 2; NaHCO 3 , 0.06; NaBr, 0.026; peptone, 5; yeast extract, 10; and glucose, 20 (Amiri et al, ; Amoozegar, Samareh‐Abolhasani, Shafiei, Didari, & Hamedi, ). For preculture, a modified medium containing (g/L): MgCl 2 , 0.7; MgSO4, 0.9; peptone, 3; yeast extract, 1; and glucose, 50 was used to adapt the Nesterenkonia for the next stage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nesterenkonia sp. strain F was cultivated in petri‐dish consisting of (g/L): NaCl, 10; MgCl 2 , 7; MgSO 4 , 9.6; CaCl 2 , 0.36; KCl, 2; NaHCO 3 , 0.06; NaBr, 0.026; peptone, 5; yeast extract, 10; and glucose, 20 (Amiri et al, ; Amoozegar, Samareh‐Abolhasani, Shafiei, Didari, & Hamedi, ). For preculture, a modified medium containing (g/L): MgCl 2 , 0.7; MgSO4, 0.9; peptone, 3; yeast extract, 1; and glucose, 50 was used to adapt the Nesterenkonia for the next stage.…”
Section: Methodsmentioning
confidence: 99%
“…C. acetobutylicum and C. beijerinckii are highly sensitive to the external environment, for example, oxygen concentration, osmotic pressure, and phenolic compounds. In our previous study, it was found that Clostridia are not the only microorganisms for biobutanol production (Amiri et al, 2016). It was demonstrated that a wild bacterium from Nesterenkonia genus could produce butanol and butyric acid along with acetone and acetic acid even in aerobic and halophilic conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A halophilic bacterium Nesterenkonia sp. F can tolerate organic solvents and produce α-amylase, and it is the only wild bacterium that can produce butanol and ethanol except Clostridia (Amiri et al, 2016). Many enzymes, such as α-amylase, β-amylase, glucoamylase, lipase, esterase, hemicellulose, and ligninase of a halophilic and halotolerant bacterial origin hold potential industrial applications, such as bioethanol, biodiesel, or fatty acids production using renewable resources (Schreck and Grunden, 2014;Elmansy et al, 2018;Amoozegar et al, 2019).…”
Section: Halophiles and Halotolerantmentioning
confidence: 99%
“…Although most butanol producers are strictly anaerobic, the halophile Nesterenkonia sp. strain F has also been reported to produce ABE from glucose under aerobic conditions (Amiri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%